2020
DOI: 10.1016/j.bcp.2019.113777
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drug discovery against arthritogenic alphaviruses: Tools and molecular targets

Abstract: Alphaviruses are (mainly) arthropod-borne viruses that belong to the family of the Togaviridae. Based on the disease they cause, alphaviruses are divided into an arthritogenic and an encephalitic group. Arthritogenic alphaviruses such as the chikungunya virus (CHIKV), the Ross River virus (RRV) and the Mayaro virus (MAYV) have become a serious public health concern in recent years. Epidemics are associated with high morbidity and the infections cause in many patients debilitating joint pain that can persist fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…This may be related to the nasal inoculation of CHIKV Ross. CHIKV Ross exhibited a certain neurotoxicity (39). Previous studies have shown that infection with CHIKV Ross can damage brain tissue in mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the nasal inoculation of CHIKV Ross. CHIKV Ross exhibited a certain neurotoxicity (39). Previous studies have shown that infection with CHIKV Ross can damage brain tissue in mice (40).…”
Section: Discussionmentioning
confidence: 99%
“…With the support of our esteemed professor, we presented a multi-country survey of COVID-19 to characterize mortality-associated factors in elderly males with comorbidities [111] . In addition to remdesivir and dexamethasone, many strategies are still under development to treat COVID-19 [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] .…”
Section: The Life-long Passion For Teaching and Researchmentioning
confidence: 99%
“…Only few of the reported molecules have been tested in alphavirus infection models so far. Infection models in small animals are available for several alphaviruses [ 1 ], but the existing models have limitations since they do not recapitulate all the key aspects of alphavirus disease in humans.…”
Section: Perspectivesmentioning
confidence: 99%
“…Alphaviruses are a group of human and animal viruses that belong to the family Togaviridae. Alphaviruses are mainly transmitted by the bite of hematophagous arthropods (e.g., ticks and mosquitoes) [ 1 ]. Classically, alphaviruses are divided into the New World and Old World alphaviruses based on their historical geographical abundance.…”
Section: Introductionmentioning
confidence: 99%